Parallel Multi-Objective Evolutionary Algorithms: A Comprehensive Survey - Falcón-Cardona, Jesús Guillermo; Hernández Gómez, Raquel; Coello Coello, Carlos A.; Castillo Tapia, Ma. Guadalupe (Swarm and evolutionary computation, 2021)
Multi-Objective Evolutionary Algorithms (MOEAs) are powerful search techniques that have been extensively used to solve difficult problems in a wide variety of disciplines. However, they can be very demanding in terms of computational resources. Parallel implementations of MOEAs (pMOEAs) provide considerable gains regarding performance and scalability and, therefore, their relevance in tackling computationally expensive applications. This paper presents a survey of pMOEAs, describing a refined taxonomy, an up-to-date review of methods and the key contributions to the field. Furthermore, some of the open questions that require further research are also briefly discussed.